The Dynamics of Islamic Educational Institutions Management - Astuti, Siwi; Ansori, M. Afif; Andari, An An (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2024)
This research aims to explain the dynamics of Mathla’ul Anwar educational institution from a management perspective. This research type is qualitative with a Library Research approach. The research data is in the form of data about The dynamics of Mathla’ul Anwareducational institution from its management aspect from primary sources in the form of books on the dynamics of educational institutions, Mathla'ul Anwar educational institutions, book development institutions in Islamic education and relevant journals. Data collection techniques were carried out using documentation studies. The researchers' data sources were obtained from books and journals about the dynamics of Mathla’ul Anwar educational institution from a management perspective. Data analysis uses Content Analysis. Based on the research results obtained, the dynamics of Mathla’ul Anwar educational institution in terms of management shows that this institution has succeeded in integrating various important elements in education to achieve its main goals. With a strong historical background and commitment to Islamic values, Mathla'ul Anwar continues to innovate and adapt to changing times. Management aspects, which include planning strategies, organizational structure, curriculum development, monitoring, and evaluation, as well as the development of human resources and facilities, have been implemented well. Overall, effective and efficient management at Mathla'ul Anwar has produced an educational institution that not only focuses on academic achievement but also builds the character and morals of students. This institution is able to face challenges and make good use of opportunities, continuing to be committed to producing a generation of knowledge, faith, and piety. Through good management, it is hoped that Mathla'ul Anwar can continue to make a meaningful contribution to the progress of education in Indonesia. Thus, this conclusion shows that the Mathla'ul Anwar educational institution continues to innovate and adapt to changing times and can make a positive contribution to creating a better educational institution.